2021
DOI: 10.1002/elsa.202100053
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale characterization of the site‐specific degradation of electric double‐layer capacitor using scanning electrochemical cell microscopy

Abstract: Electric double‐layer capacitors (EDLCs) that store electrical energy in the interface between an electrolyte and a solid electrode are favorable energy storage systems that demonstrate high‐power density, excellent cycle stability, and low environmental impact. To increase the operating voltage and improve the capacitance of EDLCs, it is essential to investigate the relationship between the degradation process and structural properties of activated carbon. In the current study, we used scanning electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Sequentially positioning the nanopipette at an array of points across the substrate surface and performing an electrochemical characterization at each point creates a nanoscale electrochemical map. SECCM is used to quantify reactions and processes at a wide variety of electrochemical interfaces with nanoscale spatial resolution, including corrosion, phase formation, surface defect detection, battery materials, and electrocatalytic reactions (e.g., hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, etc.) on single particles. …”
mentioning
confidence: 99%
“…Sequentially positioning the nanopipette at an array of points across the substrate surface and performing an electrochemical characterization at each point creates a nanoscale electrochemical map. SECCM is used to quantify reactions and processes at a wide variety of electrochemical interfaces with nanoscale spatial resolution, including corrosion, phase formation, surface defect detection, battery materials, and electrocatalytic reactions (e.g., hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, etc.) on single particles. …”
mentioning
confidence: 99%
“…The local degradation of an electrical double layer capacitor was investigated using HOPG as a substrate, and site-specific electrolyte decomposition was visualized via spatially resolved SECCM cyclic voltammetry measurements. 246 SECCM was further employed to interrogate the electrochemical activity of Fe(CN) 6 3−/4− at boron-doped diamond (BDD). The surfaces of single-crystal particles (Figure 6B) and polycrystalline electrodes were mapped, 247 and the role of BDD surface terminations on the electron transfer rate was identified.…”
Section: Electrochemical Cell Microscopymentioning
confidence: 99%
“…Characterization of electrochemically heterogeneous surfaces, from the micro- to the nanoscale, is the primary focus of SECCM studies. The local degradation of an electrical double layer capacitor was investigated using HOPG as a substrate, and site-specific electrolyte decomposition was visualized via spatially resolved SECCM cyclic voltammetry measurements . SECCM was further employed to interrogate the electrochemical activity of Fe­(CN) 6 3–/4– at boron-doped diamond (BDD).…”
Section: High-throughput Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
“…Further to this study of pseudocapacitive materials, a study by Kawabe et al was conducted which demonstrated the ability of SECCM to study electric double-layer capacitance on HOPG. 131 The authors were able to measure the degradation of the capacitance at the nanoscale, and measure the increase in the degradation at HOPG edge sites.…”
Section: Energy Storage Materialsmentioning
confidence: 99%